Primary laparoscopic fundoplication in selected patients with gastroesophageal reflux disease. Issue 1 (18th May 2021) - Fuchs, K H; Breithaupt, W; Varga, G; Babic, B; Schulz, T; Meining, A
Summary: Background: Despite proton pump inhibitors being a powerful therapeutic tool, laparoscopic fundoplication (LF) has proven successful in the treatment of gastroesophageal reflux disease (GERD), through mechanical augmentation of a weak antireflux barrier and the advantages of minimally invasive access. A critical patient selection for LF, based on thorough preoperative assessment, is important for the management of GERD-patients. The purpose of this study is to provide an overview on the management of GERD-patients treated by primary LF in a specialized center and to illustrate the possible outcome after several years. Methods: Patients were selected after going through diagnostic workup consisting of patient's history and physical examination, upper gastrointestinal endoscopy, assessment of gastrointestinal Quality of Life Index, screening for somatoform disorders, functional assessment by esophageal manometry, (impedance)-24-hour-pH-monitoring, and selective radiographic studies. The indication for LF was based on EAES-guidelines. Either a floppy and short Nissen fundoplication was performed or a posterior Toupet-hemifundoplication was chosen. A long-term follow-up assessment was attempted after surgery. Results: In total, n = 1131 patients were evaluated (603 males; 528 females; mean age; 48.3 years; and mean body mass index: 27). The mean duration between onset of symptoms and surgery was 8 years. Nissen: n = 873, Toupet: n = 258; conversion rateerativ: 0.5%; morbidity 4%, mortality: 1 (1131). Mean follow-up ( n = 898; 79%): 5.6 years; pre/post-op results: esophagitis: 66%/12.1%; Gastrointestinal Quality of Life Index: median: 92/119; daily proton pump inhibitors-intake after surgery: 8%; and operative revisions 4.3%. Conclusions: In conclusion, our data show that careful patient selection for laparoscopic fundoplication and well-established technical concepts of mechanical sphincter augmentation can provide satisfying results in the majority of patients with severe GERD.